2016
DOI: 10.1111/jocn.13298
|View full text |Cite
|
Sign up to set email alerts
|

Being an informal caregiver for a relative with liver cirrhosis and overt hepatic encephalopathy: a phenomenological study

Abstract: Nurses should acknowledge caregivers as experts in caring for their loved ones. Nurses can assist caregivers in managing an episode of hepatic encephalopathy and can provide individualised interventions to ease the future burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 29 publications
0
43
0
2
Order By: Relevance
“…This reduced quality of life has an impact of the clinical course of the patients. Frequently, relatives are the first who register initially subtle changes in patients, for example in hepatic encephalopathy, and initiate first steps of therapy [13]. Studies on psychosocial stress of caregivers in chronic diseases such as dementia or ALS have shown that the degree of psychosocial stress even correlates with mortality in relatives and caregivers [14].…”
Section: Discussionmentioning
confidence: 99%
“…This reduced quality of life has an impact of the clinical course of the patients. Frequently, relatives are the first who register initially subtle changes in patients, for example in hepatic encephalopathy, and initiate first steps of therapy [13]. Studies on psychosocial stress of caregivers in chronic diseases such as dementia or ALS have shown that the degree of psychosocial stress even correlates with mortality in relatives and caregivers [14].…”
Section: Discussionmentioning
confidence: 99%
“…Since the scale encompasses most recognizable risk factors for hepatic encephalopathy, some relevant educational materials could be designed to help the patients acquire relevant preventive knowledge and adopt methods for early prevention [24]. As a result, the patients who are at risk may bene t from more frequent support and education of caregivers and may learn to prevent falls and recurrence with the help of precise advice [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the limited research available, informal caregivers of patients with ESLD are depressed (Malik et al, 2014) and feel overwhelmed (Kunzler-Heule, Beckmann, Mahrer-Imhof, Semela, & Handler-Schuster, 2016). They experience uncertainty, fears (Meltzer & Rodrigue, 2001), and significant caregiver strain (Bajaj et al, 2011;Miyazaki et al, 2010).…”
Section: Physical and Psychological Symptoms In Caregivers Of Patiementioning
confidence: 99%